PHYSICO-CHEMICAL PARAMETERS OF IMPHAL RIVER, MANIPUR - DEVI, W. SURAJ; SINGH, K. H. RAJMANI (Journal of the Inland Fisheries Society of India, 2021)
Rivers are the most important freshwater resource for human being. Assessments of river water quality have been made by various workers in India. (Sharma and Agrawal, 1999; Baruah and Baruah, 2003; Kumar, 2003; Kulsherstha and Sharma, 2006). In Manipur there are numerous rivers and streams, which are directly or indirectly feeding the important lakes of the state and many of them enhane the process of eutrophication and pollution in the lake ecosystems (Singh and Singh, 1994). However, there are few reports on the status of riverine ecosystem of the state (Rajeshwari Devi 2005,). The physico-chemical characteristics depend on discharge of domestic, municipal, industrial and other several factors like religious offerings, recreational and constructional activities in the catchment areas (Panda et al., 1991). Imphal River is one of the important rivers, which flows into the Loktak Lake in Manipur while passing through Lilong, Mayang Imphal and loses its purity by collecting all the domestic waste from the surrounding town. The present study has been carried out with the objectives to assess the seasonal variation as well as water quality status based on some physico-chemical characteristics of Imphal River.